Digital Economic Dynamics Innovations, Networks and Regulations - Welfens, Paul J.J.; Welfens, Paul J.J.; Weske, Mathias.; Weske, Mathias. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
The 21st century is increasingly shaped by the expansion of software applications and digital networking. This book analyzes the dynamics and impacts of software development and discusses new institutional and economic changes in the context of digital market economies. Regulatory approaches in OECD countries are compared and country studies evaluated with respect to innovation and welfare aspects. The book furthermore examines telecommunications regulation of fixed line networks, cable TV and mobile communications. There is also focus on the role of EU framework regulation and issues of market power as well as Schumpeterian dynamics.